The Association of Labor Induction for Advanced Maternal Age With Cesarean Section [23L]. (May 2017) - Spiegelman, Jessica; Connolly, Katherine; Khander, Amrin; Factor, Stephanie; Stone, Joanne
Abstract : INTRODUCTION: To determine if induction of labor among women ≥ 40 years for advanced maternal age (AMA) at 39 0/7–39 6/7 weeks is associated with an increased risk of cesarean section compared to women who are expectantly managed. METHODS: A retrospective cohort study of patients ≥ 40 years who delivered at a single tertiary care center from June 2011 through December 2014. Cesarean section rates of women who underwent induction of labor at 39 0/7-39 6/7 weeks for AMA to those who were expectantly managed were compared using chi-square and multiple logistical regression. RESULTS: Of 223 nulliparous women, 76 (34%) were in the induction group, and of the 263 multiparous women, 85 (32%) were in the induction group. Among the nulliparous women, there were no differences in baseline characteristics. Among the multiparous women, those in the induction group were older (median age 42 vs. 41, P=.01) and had a lower admission Bishop Score (median 9 vs. 10, P=.05). Among nulliparous women, the induction group was not at increased risk of cesarean section (OR=1.47, 95%CI 0.84, 2.58, P=.18). Among multiparous women, the induction group was not at increased risk of cesarean section (OR=1.69, 95% CI 0.71, 3.99, P=.23) after controlling for age and admission Bishop Score. CONCLUSION: In patients ≥ 40 years old, induction of labor for AMA was not associated with an increased risk of cesarean section. Given the concern for stillbirth in this group, this information may help guide clinicians decide whether to induce labor for AMA in the absence of other indications.